2019
DOI: 10.1111/acer.14039
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 is Increased in Cerebrospinal Fluid of Individuals With Alcohol Use Disorder

Abstract: Background: Recent studies have shown that alcohol use affects the regulation and expression of proprotein convertase subtilisin/kexin 9 (PCSK9). While a major role of PCSK9 in hepatic function and lipid regulation has been clearly established, other pleiotropic effects remain poorly understood. Existing research suggests a positive association between PCSK9 expression in the brain and psychopathology, with increased levels of PCSK9 in the cerebrospinal fluid (CSF) of individuals with dementia and epigenetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 70 publications
0
19
1
Order By: Relevance
“…The reason for this phenomenon may be that plasma PCSK9 levels are influenced by hormones such as estrogen [ 39 ]. Besides, we found that low PCSK9 levels were associated with the feature of smoking and drinking was inconsistent with other studies [ 40 , 41 ], which may need to investigate further in a large sample study.…”
Section: Discussioncontrasting
confidence: 98%
“…The reason for this phenomenon may be that plasma PCSK9 levels are influenced by hormones such as estrogen [ 39 ]. Besides, we found that low PCSK9 levels were associated with the feature of smoking and drinking was inconsistent with other studies [ 40 , 41 ], which may need to investigate further in a large sample study.…”
Section: Discussioncontrasting
confidence: 98%
“…In the context of CV prediction, PCSK9 concentrations, increased by insulin-resistance [ 18 ], are also associated with a raised susceptibility to MI, as assessed by genome association studies [ 19 ], although data from epidemiological studies are discordant [ 20 23 ]. The association between mood disorders and PCSK9 levels have received a significant contribution from a recent study on subjects affected by alcohol use disorder showing that PCSK9 cerebrospinal fluid levels are associated with the severity of behavioral disturbances [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this this version posted October 7, 2020. ; https://doi.org/10.1101/2020. 10 disorder, including the interesting possibility of using anti-PSCK9 monoclonal antibodies for the treatment of alcoholic liver disease [63,64]. Given that alcohol is a well-known risk factor for HNSCC, this pleiotropy could have partially explained the effect seen in our study, however we proxied the inhibition of PCSK9 and so would have expected to see a protective effect of this gene in HNSCC cases who may have been heavy alcohol drinkers.…”
Section: Discussionmentioning
confidence: 94%